Anti-Arthritic Effect of the Hydroethanolic Root Extract of Psydrax subcordata in Rats - Phyllis Annan; Newman Osafo; Paul Poku Sampene Ossei; Wonder Kofi Mensah Abotsi (Advances in Pharmacological and Pharmaceutical Sciences)
Background. In Ghana, decoctions of various parts of Psydrax subcordata, Bridson (Rubiaceae) are employed in the management of inflammatory conditions. However, not much scientific data is available to back such folkloric use of the plant. This study, therefore, seeks to investigate the chronic anti-inflammatory activity of hydroethanolic root extract of Psydrax subcordata (PSRE) using the adjuvant-induced arthritis model in rats. Methods. Freund’s adjuvant-induced arthritis model was used to assess the ameliorative effects of PSRE in chronic inflammation. The effect of PSRE on tissue and joint integrity in arthritis was also evaluated by histopathology and microscopy. The effect of PSRE on oxidative markers and serum transforming growth factor (TGF) beta 1 was also determined via chemical assays. Results. Oral PSRE (30–300 mg/kg) inhibited both ipsilateral and contralateral paw arthritis when given prophylactically and therapeutically in rats. It reduced paw defect on X-ray with histologically-reduced inflammatory cells and synovial hyperplasia. Finally, PSRE significantly reduced TGF-beta 1 levels and raised antioxidants such as reduced glutathione, catalase, and superoxide dismutase levels in arthritic rats. Conclusion. The findings show that hydroethanolic root extract of Psydrax subcordata possesses anti-inflammatory properties in rodents.